Pushing the frontiers of Nigeria's cultural communication through digital media practice. Issue 2 (1st December 2020) - Morgan, Trevor Vermont
This article uses the example of a digital Nigeria visualization and animation project to provide an insight into the kind of technological, cultural and communication possibilities available for indigenous groups of Africa, and Nigeria in particular. This follows the nascent dispersal of the digital three-dimensional media production experiences in Nigeria. The project has used digital media technology to capture visual elements of different cultural elements amongst the Igbo of Nigeria as a means of promoting identity and cultural longevity. An overview of the development of digital 3D animation in Nigeria has been used to locate the project in the stream of contemporary practice so as to provide the right context for its appreciation.